2022
DOI: 10.1021/acsnano.2c01252
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Lipid Bilayer Nanocarriers for Cancer Immunotherapy in Heterogeneous Tumor Microenvironments, Combining Immunogenic Cell Death Stimuli with Immune Modulatory Drugs

Abstract: In addition to the contribution of cancer cells, the solid tumor microenvironment (TME) has a critical role in determining tumor expansion, antitumor immunity, and the response to immunotherapy. Understanding the details of the complex interplay between cancer cells and components of the TME provides an unprecedented opportunity to explore combination therapy for intervening in the immune landscape to improve immunotherapy outcome. One approach is the introduction of multifunctional nanocarriers, capable of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 306 publications
2
41
0
Order By: Relevance
“…Moreover, further experimentation in a robust orthotopic KPC model confirmed the ability of the dual-delivery carrier to trigger a synergistic immune response, backed by data showing improved drug delivery and tumor biodistribution. Not only do these results demonstrate the efficacy of a co-formulated drug carrier, but they expand the scope of employing a chemo-immunotherapy approach for PDAC and other cancers, as recently reviewed by us …”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Moreover, further experimentation in a robust orthotopic KPC model confirmed the ability of the dual-delivery carrier to trigger a synergistic immune response, backed by data showing improved drug delivery and tumor biodistribution. Not only do these results demonstrate the efficacy of a co-formulated drug carrier, but they expand the scope of employing a chemo-immunotherapy approach for PDAC and other cancers, as recently reviewed by us …”
Section: Resultssupporting
confidence: 60%
“…While genetically engineered Pdx1-cre/LSL-Kras/G12D/p53R172H mice display many similarities to human PDAC (including the G12D KRAS mutation and TP53 loss, extensive desmoplasia, and an immune suppressive TME), the logistical constraints of animal breeding prompted us to use an orthotopic model instead. We have previously shown that implantation of a luciferase-expressing KPC cell line into the pancreatic tail of immunocompetent B6129SF1/J mice can be used to obtain tumor growth, with retention of human PDAC features, including a more robust stroma that resembles the heterogeneous immune landscape of the genetic animal models …”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations